Inventory development for perfluorooctane sulfonic acid (PFOS) in Turkey: challenges to control chemicals in articles and products - Korucu, Mahmut Kemal; Gedik, Kadir; Weber, Roland; Karademir, Aykan; Kurt Karakuş, Perihan Binnur (Springer Heidelberg, 2015)
Perfluorooctane sulfonic acid (PFOS) and related substances have been listed as persistent organic pollutants (POPs) in the Stockholm Convention. Countries which have ratified the Convention need to take appropriate actions to control PFOS use and release. This study compiles and enhances the findings of the first inventory of PFOS and related substances use in Turkey conducted within the frame of the Stockholm Convention National Implementation Plan (NIP) update. The specific Harmonized Commodity Description and Coding System (Harmonized System (HS)) codes of imported and exported goods that possibly contain PFOS and 165 of Chemical Abstracts Service (CAS) numbers of PFOS-related substances were assessed for acquiring information from customs and other authorities. However, with the current approaches available, no useful information could be compiled since HS codes are not specific enough and CAS numbers are not used by customs. Furthermore, the cut-off volume in chemical databases in Turkey and the reporting limit in the HS system (0.1 %) are too high for controlling PFOS. The attempt of modeling imported volumes by a Monte Carlo simulation did not also result in a satisfactory estimate, giving an upper-bound estimate above the global production volumes. The replies to questionnaires were not satisfactory, highlighting that an elaborated approach is needed in the communication with potentially PFOS-using stakeholders. The experience of the challenges of gathering information on PFOS in articles and products revealed the gaps of controlling highly hazardous substances in products and articles and the need of improvements.
12th Forum of the International-HCH-and-Pesticides-Association (IHPA) -- NOV 06-08, 2013 -- Kiev, UKRAINE
Keywords: Chemicals in products; HS codes; Monte Carlo simulation; POPs inventory; PFOS and PFAS; Stockholm Convention